Tongzhi living : men attracted to men in postsocialist China - Zheng, Tiantian (University of Minnesota Press, 2015)
Tongzhi, which translates into English as "same purpose" or "same will," was once widely used to mean "comrade." Since the 1990s, the word has been appropriated by the LGBT community in China and now refers to a broad range of people who do not espouse heteronormativity. Tongzhi Living, the first study of its kind, offers insights into the community of same-sex-attracted men in the metropolitan city of Dalian in northeast China. Based on ethnographic fieldwork by Tiantian Zheng, the book reveals an array of coping mechanisms developed by tongzhi men in response to rapid social, cultural, and political transformations in postsocialist China. According to Zheng, unlike gay men in the West over the past three decades, tongzhi men in China have adopted the prevailing moral ideal of heterosexuality and pursued membership in the dominant culture at the same time they have endeavored to establish a tongzhi culture. They are, therefore, caught in a constant tension of embracing and contesting normality as they try to create a new and legitimate space for themselves. Tongzhi men's attempts to practice both conformity and rebellion paradoxically undercut the goals they aspire to reach, Zheng shows, perpetuating social prejudice against them and thwarting the activism they believe they are advocating